Studi Kasus Dampak Gaya Kepemimpinan Kepala Sekolah Terhadap Kepuasan dan Motivasi Kerja Guru di Sekolah XYZ (Indo-MathEdu Intellectuals Journal, 2025)
This study is motivated by the declining job satisfaction and work motivation of teachers at XYZ School, which is suspected to be influenced by the principal’s leadership style. The theoretical framework includes leadership style theories (transformational, transactional, authoritarian, participative), Herzberg’s job satisfaction theory, and motivation theories from Maslow and the two-factor theory. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with teachers and students, observations, and document analysis. Data analysis was conducted using the interactive model from Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that the principal’s leadership style—closed, authoritarian, and non-participative—negatively affects teachers’ job satisfaction and motivation. Teachers feel excluded from decision-making, experience unfair treatment, and lack professional support. Moreover, the change in leadership has led to deteriorating relationships between the principal and teachers, marked by social divisions, distrust, and weakened collaboration. The school climate has become tense, discouraging both professional growth and educational quality. Non-inclusive leadership styles negatively impact the work climate in schools and lower the overall quality of education.